2010
DOI: 10.1111/j.1551-6709.2010.01102.x
|View full text |Cite
|
Sign up to set email alerts
|

Gesturing Saves Cognitive Resources When Talking About Nonpresent Objects

Abstract: In numerous experimental contexts, gesturing has been shown to lighten a speaker’s cognitive load. However, in all of these experimental paradigms, the gestures have been directed to items in the ‘here-and-now’. This study attempts to generalize gesture’s ability to lighten cognitive load. We demonstrate here that gesturing continues to confer cognitive benefits when speakers talk about objects that are not present, and therefore cannot be directly indexed by gesture. These findings suggest that gesturing conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(143 citation statements)
references
References 30 publications
7
131
1
4
Order By: Relevance
“…Following the original finding of Goldin-Meadow et al (2001) that participants remembered more letters when they were gesturing than when they were not gesturing during the explanation, further studies have shown that this effect is independent of the type of to-beremembered items (spatial patterns vs. letters; Wagner et al, 2004) or the presence of a visual representation of the problem (Ping & Goldin-Meadow, 2010). This suggests that the effect is general and does not relate on a specific form of encoding or maintenance of information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the original finding of Goldin-Meadow et al (2001) that participants remembered more letters when they were gesturing than when they were not gesturing during the explanation, further studies have shown that this effect is independent of the type of to-beremembered items (spatial patterns vs. letters; Wagner et al, 2004) or the presence of a visual representation of the problem (Ping & Goldin-Meadow, 2010). This suggests that the effect is general and does not relate on a specific form of encoding or maintenance of information.…”
Section: Discussionmentioning
confidence: 99%
“…It varies widely among individuals and correlates with many cognitive processes, such as general fluid intelligence, problem solving, planning, or language comprehension (Engle, Tuholski, Laughlin, & Conway, 1999;Kane et al, 2004;Unsworth, Redick, Heitz, Broadway, & Engle, 2009). Recently, a few studies from the emerging field of gesture research have also related WM to the production of co-speech gestures and have shown a gesture effect on working memory-that is, an increase in WM accuracy due to gesturing (Cook, Yip, & Goldin-Meadow, 2011;Goldin-Meadow, Nusbaum, Kelly, & Wagner, 2001;Ping & Goldin-Meadow, 2010;Wagner, Nusbaum, & Goldin-Meadow, 2004). Co-speech gestures are meaningful hand movements that are semantically and temporally integrated with the speech they accompany.…”
Section: Introductionmentioning
confidence: 99%
“…For example, participants did better in their task when explaining mathematics (Cook, Yip, & Goldin-Meadow, 2012; Susan Goldin-Meadow, Nusbaum, Kelly, & Wagner, 2001). Even when people refer to objects that are not present, they perform better if they are allowed to gesture (Ping & Goldin-Meadow, 2010). Adding a gesture to a word is not unnatural redundancy, as it happens thousands of times a day.…”
Section: Why the Body Helps The Mindmentioning
confidence: 99%
“…Indeed, speakers are more fluent, producing fewer errors and verbal hesitations, when they are permitted to gesture than when they are prevented from gesturing [31,32]. Gesturing while speaking also frees up working memory: speakers find it easier to remember a list of unrelated items when they gesture while talking than when they do not gesture [33][34][35]. Gesturing also provides kinaesthetic and visual feedback that can directly aid problem-solving.…”
Section: Gesture and Thoughtmentioning
confidence: 99%